2020
DOI: 10.1017/s0954579420001315
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and socioeconomic status in early childhood: A multidimensional assessment

Abstract: The hypothalamic–pituitary–adrenal (HPA) axis is sensitive to early life stress, with enduring consequences for biological stress vulnerability and health (Gunnar & Talge, 2008). Low socioeconomic status (SES) is associated with dysregulation of the stress hormone cortisol in early childhood. However, a mechanistic understanding of this association is lacking. Multidimensional assessment of both SES and cortisol is needed to characterize the intricate relations between SES and cortisol function in early ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 66 publications
(102 reference statements)
3
34
1
Order By: Relevance
“…Parental sensitivity was unrelated to the infant cortisol measures. Despite finding a connection between parental sensitivity and HCC, parental sensitivity was not found to mediate links between SES risks and HCC in the 12-month-old group or 3.5-year-old group [52]. These results suggest that the interactions between parent sensitivity and child hair cortisol are likely to be complex, and it would therefore be beneficial for researchers to utilize the entirety of the EA Scales in order to more accurately observe how SES risks may play a role in parenting and child cortisol functioning.…”
Section: Stress Physiologycontrasting
confidence: 60%
See 2 more Smart Citations
“…Parental sensitivity was unrelated to the infant cortisol measures. Despite finding a connection between parental sensitivity and HCC, parental sensitivity was not found to mediate links between SES risks and HCC in the 12-month-old group or 3.5-year-old group [52]. These results suggest that the interactions between parent sensitivity and child hair cortisol are likely to be complex, and it would therefore be beneficial for researchers to utilize the entirety of the EA Scales in order to more accurately observe how SES risks may play a role in parenting and child cortisol functioning.…”
Section: Stress Physiologycontrasting
confidence: 60%
“…Their indirect effect finding suggested that a lower ITN ratio was linked to elevated amygdala responses to negative infant faces, and this was further associated with lower nonintrusiveness (meaning the mother was observed to be more intrusive) during the interaction. Similarly to the study by Tarullo, Tuladhar, Kao, Drury and Meyer [52], there was no effect for maternal sensitivity [71]. This finding has huge implications for future interventions for low-income mothers, who may be more vulnerable to altered neural processing of emotional expressions, and calls for more research on the links between SES, stress physiology, neural processing, and all of the EA Scales.…”
Section: Normative Samplesmentioning
confidence: 51%
See 1 more Smart Citation
“…Contrarily, men who experienced any form of FI had longer sleep latencies than fully food-secure men [ 21 ]. A biological model involving the hypothalamic–pituitary–adrenal axis has been proposed to understand the process of how FI perturbs physical functions [ 22 , 23 ]. In a study on monkeys, food-deprived female monkeys manifested marked individual cortisol responses and compromised normative maternal–infant rearing behaviors [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Family routines may help to mitigate the effects of chronic stress by establishing predictability and structure within the environment (Larsen & Jordan, 2020). Indeed, multiple research teams have identified associations between household chaos and child HPA axis functioning (e.g., Brown et al, 2019;Doom et al, 2018;Tarullo et al, 2020). For example, experiencing more household chaos during preschool has been found to predict a more blunted diurnal cortisol slope during middle childhood (Doom et al, 2018;Larsen & Jordan, 2020).…”
Section: Introductionmentioning
confidence: 99%